2011
DOI: 10.3399/bjgp11x572391
|View full text |Cite
|
Sign up to set email alerts
|

Identifying suspected breast cancer: development and validation of a clinical prediction rule

Abstract: BackgroundAn evidence-based approach is needed to identify women with breast symptoms who are most likely to have breast cancer so that timely and appropriate referral can take place. AimTo report the development and validation of a clinical prediction rule for the diagnosis of breast cancer. Design and settingCohort study with two prospective groups of women: those presenting to a symptomatic breast clinic (derivation cohort) and a separate cohort presenting to 11 general practices (validation cohort) in Tays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
3
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 30 publications
(38 reference statements)
0
23
3
1
Order By: Relevance
“…For example, there is some evidence that the sensitivity and specificity of ultrasound is greater than mammography in patients with breast symptoms for the detection of cancer, especially in younger women (23). More granular NBCCEDP monitoring tools, or the development of clinical prediction rules (24) may also be possible to encourage providers to deliver appropriate and timely follow-up for certain women with breast symptoms who may be at higher risk for cancer (24). Our results, along with evidence-based guidelines, can aid clinicians in the evaluation and diagnosis of many breast concerns.…”
Section: Discussionmentioning
confidence: 99%
“…For example, there is some evidence that the sensitivity and specificity of ultrasound is greater than mammography in patients with breast symptoms for the detection of cancer, especially in younger women (23). More granular NBCCEDP monitoring tools, or the development of clinical prediction rules (24) may also be possible to encourage providers to deliver appropriate and timely follow-up for certain women with breast symptoms who may be at higher risk for cancer (24). Our results, along with evidence-based guidelines, can aid clinicians in the evaluation and diagnosis of many breast concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Still, they indicated that protocols for priority referral from primary care have a cancer detection rate of some 10% 39 and sensitivity of some 90% 39,40,41 . The sign most commonly associated with breast cancer is breast lump, present in 90% of cases confirmed subsequently as cancer 42,43,44 .…”
Section: Early Diagnosis Strategiesmentioning
confidence: 99%
“…31 This prediction rule was derived from a secondary care setting and only had 59 cases in the derivation cohort and five in the validation cohort which the authors recognise was likely to be under-powered. 31 While both the current study and McGowan's found breast lump and skin tethering and increasing age were predictive of a diagnosis of breast cancer, this study's risk ratios were substantially higher for a breast lump (risk ratio = 51 compared with odds ratio = 15) although similar for skin tethering (risk ratio =9 compared with odds ratio = 8). Unlike the McGowan study, it was found that alcohol, family history of breast cancer, breast pain, post-menopausal bleeding, increasing affluence, and venous thromboembolism were independently predictive of a diagnosis of breast cancer.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%